2020
DOI: 10.1088/1361-6641/ab9477
|View full text |Cite
|
Sign up to set email alerts
|

Porous semiconductor compounds

Abstract: In this review paper, we present a comparative analysis of the electrochemical dissolution of III-V (InP, GaAs, GaN), II-VI (ZnSe, CdSe) and SiC semiconductor compounds. The resulting morphologies are discussed, including those of porous layers and networks of low-dimensional structures such as nanowires, nanobelts, and nanomembranes. Self-organized phenomena in anodic etching are disclosed, leading to the formation of controlled porous patterns and quasi-ordered distribution of pores. Results of templated ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 281 publications
0
33
0
Order By: Relevance
“…However, according to very low catalytic activity under visible light illumination of aero-Ga 2 O 3 functionalized with Au or Pt, as deduced from Figure 6 b, one can conclude that light absorption is not extended to the visible light spectrum, indicating that the plasmonic effects of Au or Pt coatings are negligible in the prepared aero-Ga 2 O 3 catalyst. On the contrary, the improvement of the catalytic performance upon Pt deposition, and especially by Au functionalization, may come from effective carrier separation at the Schottky contact formed at the semiconductor metal interface, especially when the noble metal is in the form of dots [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, according to very low catalytic activity under visible light illumination of aero-Ga 2 O 3 functionalized with Au or Pt, as deduced from Figure 6 b, one can conclude that light absorption is not extended to the visible light spectrum, indicating that the plasmonic effects of Au or Pt coatings are negligible in the prepared aero-Ga 2 O 3 catalyst. On the contrary, the improvement of the catalytic performance upon Pt deposition, and especially by Au functionalization, may come from effective carrier separation at the Schottky contact formed at the semiconductor metal interface, especially when the noble metal is in the form of dots [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most likely, the dots are the result of the sedimentation of reaction products that occur during the electrochemical dissolution of the crystal. In general, semiconductors of the A 2 B 6 group, in contrast to semiconductors A 3 B 5 , show poor ability to structure during electrochemical treatment [26]. For example, the formation of a wide class of nanostructures on the surface of indium phosphide, gallium arsenide, and gallium phosphide is observed in a wide range of etching regimes [27,28].…”
Section: Sem Analysismentioning
confidence: 99%
“…Detailed study of the properties of such films was done in [51] According to the Auger electron spectroscopy data, 5+0.5 at.% average deviation from the starting material stoichiometry towards elemental carbon enrichment was determined within the anodic films formed in HF-based electrolytes with ethanol in several concentrations. In addition, an elemental analysis performed with electron diffraction spectroscopy showed that the films were enriched with oxygen and fluorine at the level of (5-7) at.% and (7)(8)(9)(10)(11) at.%, respectively. It was found that the samples with an increased content of detectable chemical impurities had pronounced photosensitivity.…”
Section: Porous Sic Formationmentioning
confidence: 99%
“…Here we note that Lee Canham subsequently pioneered the biomedical applications of porous silicon as well [4]. To date, there have been several generalizing reviews on the recent results of obtaining porous structures based on semiconductor materials and compounds and the prospects for their application for modern micro-and nanoelectronics, sensing and biotechnologies [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%